PENERAPAN PEMBELAJARAN MENGGUNAKAN DEDUCTIVE-INDUCTIVE SCIENCE THINKING MODEL UNTUK MENINGKATKAN PEMAHAMAN KONSEP METODE PENELITIAN PENDIDIKAN BIOLOGI DITINJAU DARI KREATIVITAS MAHASISWA - Ari Prabowo, Sigit; Setyo Retno, Raras; Utami, Sri (Jurnal Pendidikan, 2013)
The object of this study were 1) to determine the effect of deductive - Inductive Science Thinking Model on student achievement, 2) to determine the effect of creativity on learning achievement , 3) to determine the interaction between deductive-Inductive Science Thinking Model with the creativity of the learning achievement .This study used an experimental method . The population is students of Biology in semester VI IKIP PGRI Madiun academic year 2012/2013. Sampling using cluster random sampling technique that consists of two classes, one class for learning deductive - Inductive Thinking Model Science and other class on non deductive-Inductive Thinking Science Model. Hypotheses were analyzed using 2-way ANOVA with a 2x2 factorial design .The results of this study after testing the hypothesis at 95% confidence level is 1) no effect on the use of models of learning achievement , 2) there is the influence of creativity on learning achievement, 3) there is an interaction between the model of learning and creativity on learning achievement.Key words: Deductive-Inductive, creativity, learning achievement